Adaptive immunity and pathogenesis of diabetes: insights provided by the α4-integrin deficient NOD mouse - Oulghazi, Salim; Wegner, Sarah K.; Spohn, Gabriele; Müller, Nina; Harenkamp, Sabine; Stenzinger, Albrecht; Papayannopoulou, Thalia; Bönig, Halvard (Cells, 2020)
Background: The spontaneously diabetic “non-obese diabetic” (NOD) mouse is a faithful model of human type-1 diabetes (T1D). Methods: Given the pivotal role of α4 integrin (CD49d) in other autoimmune diseases, we generated NOD mice with α4-deficient hematopoiesis (NOD.α4-/-) to study the role of α4 integrin in T1D. Results: NOD.α4-/- mice developed islet-specific T-cells and antibodies, albeit quantitatively less than α4+ counterparts. Nevertheless, NOD.α4-/- mice were completely and life-long protected from diabetes and insulitis. Moreover, transplantation with isogeneic α4-/- bone marrow prevented progression to T1D of pre-diabetic NOD.α4+ mice despite significant pre-existing islet cell injury. Transfer of α4+/CD3+, but not α4+/CD4+ splenocytes from diabetic to NOD.α4-/- mice induced diabetes with short latency. Despite an only modest contribution of adoptively transferred α4+/CD3+ cells to peripheral blood, pancreas-infiltrating T-cells were exclusively graft derived, i.e., α4+. Microbiota of diabetes-resistant NOD.α4-/- and pre-diabetic NOD.α4+ mice were identical. Co- housed diabetic NOD.α4+ mice showed the characteristic diabetic dysbiosis, implying causality of diabetes for dysbiosis. Incidentally, NOD.α4-/- mice were protected from autoimmune sialitis. Conclusion: α4 is a potential target for primary or secondary prevention of T1D.